2011
DOI: 10.1007/s10903-011-9465-6
|View full text |Cite
|
Sign up to set email alerts
|

Communication and Cultural Issues in Providing Reproductive Health Care to Immigrant Women: Health Care Providers’ Experiences in Meeting Somali Women Living in Finland

Abstract: Communication problems due to language and cultural differences between health care professionals and patients are widely recognized. Finns are described as more silent whereas one concurrent large immigrant group, the Somalis, are described as more open in their communication. The aim of the study was to explore physicians-nurses/midwives' communication when providing reproductive and maternity health care to Somali women in Finland. Four individual and three focus group interviews were carried out with 10 gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 37 publications
(30 reference statements)
4
86
0
3
Order By: Relevance
“…Nevertheless, the practice is still a long-standing common cultural tradition in Somalia, where more than 90% of females are circumcised. However, not all Somali women living in Finland are comfortable with such practice (Degni 2004). A third point is that although, the scope of this study was not women's interpretation of faith; however, our observation was that our participants did not share a radical view on the use of contraception and practice of abortion.…”
Section: Somalis As a Minority In Finlandmentioning
confidence: 73%
See 1 more Smart Citation
“…Nevertheless, the practice is still a long-standing common cultural tradition in Somalia, where more than 90% of females are circumcised. However, not all Somali women living in Finland are comfortable with such practice (Degni 2004). A third point is that although, the scope of this study was not women's interpretation of faith; however, our observation was that our participants did not share a radical view on the use of contraception and practice of abortion.…”
Section: Somalis As a Minority In Finlandmentioning
confidence: 73%
“…Somalis are visible because their different culture and religion sets them apart from other Africans, and also from mainstream Finns. Degni (2004) highlighted that Somalis are a unique minority ethnic group that is vulnerable to health and social challenges because many Somalis (particularly women) had experienced considerable stress due to the social instabilities and violent circumstances they encountered in their homeland. Nevertheless, Somalis in Finland cannot be considered a homogenous group with uniform sets of belief practices, customs and needs because beliefs might find different expressions in practice among individuals of the same culture, religion and language (Alitolppa-Niitamo 1994).…”
Section: Somalis As a Minority In Finlandmentioning
confidence: 99%
“…[47,52] In four studies, ICC was facilitated when the doctor was aware of his own culture. [31,43,110,111] For doctors, another main objective in ICC was to manage patients' expectations of the health care system. For example, it was often reported that patients with different ethnic backgrounds did not know how to enter the healthcare system, how to make an appointment with the doctor or which person with a high social status and regarded it as disrespectful to contradict the doctor (paternalism).…”
Section: Differences In Cultural Perception Of Illness and Diseasementioning
confidence: 99%
“…For example, it was often reported that patients with different ethnic backgrounds did not know how to enter the healthcare system, how to make an appointment with the doctor or which person with a high social status and regarded it as disrespectful to contradict the doctor (paternalism). [43,72,79,88,90,97,[122][123][124]127,[130][131][132][133][134][135][136][137][138][139][140] In these cases, patient-centered communication might be a effective approach for ICC.…”
Section: Differences In Cultural Perception Of Illness and Diseasementioning
confidence: 99%
See 1 more Smart Citation